ICE STORAGE CHARACTERISTICS OF CULTURED MACRO BRACHIUM ROSENBERG II (DE MAN - RODRIGUES, FANITA; BASU, SUBRATA; HAZRA, ANSUMAN (Journal of Indian Fisheries Association, 2016)
CulturedMacrobrachium rosenbergii (Scampi; 30-40 g) in headless shell-on form was stored in ice (Prawn:ice=l:2) in a plywood box insulated with 2 em thick expanded polystyrene and subjected to detailed examination of quality by chemical, microbiological and organoleptic evaluation at regular intervals to assess the storage life. The prime quality life of prawns in ice was found to be 8 days followed by a phase of lowered quality, but still acceptable till the end of 13 days. Keywards : Ice storage characteristics, M. resenbergii, storage life